Decision making for network security with simple additive weighting method - Andi Zulherry (Institute of Computer Science (IOCS), 2023)
In an increasingly complex digital era, network security has become a crucial aspect in maintaining data integrity, confidentiality, and availability. Effective decision-making methods to select the right network security solution are becoming increasingly important. This article describes the application of the Simple Additive Weighting (SAW) method as a support tool in the context of decision-making for network security. In the presented case study, three network security solutions are evaluated based on four important criteria: data encryption level, threat detection, access management, and network performance. The SAW method is used to assign weights to each criterion and generate a ranking of solutions based on the final score. The results show that SAW provides a clear and structured view of the network security solution that best fits the user's needs and priorities. The conclusion of this research is that the SAW method can be used as a useful tool in making informed decisions in the context of network security. SAW allows organizations to adjust their priorities by setting the appropriate criteria weights, thus enabling the selection of solutions that are best suited to the unique needs of each organization. In an era of ever-evolving cyber threats, the ability to make effective decisions in the face of security challenges is becoming increasingly important, and the SAW method can be a valuable tool in achieving that goal.